Advanced freezing point insights into regulatory role of antifreeze proteins, their fundamentals, and obstacles in food preservation - Eskandari, Azadeh; Leow, Thean Chor; Abdul Rahman, Mohd Basyaruddin; Oslan, Siti Nurbaya (Springer, 2024)
Freezing, a technique extensively employed within the food industry, is considered to be among the most prevalent preservation methods. Conventional techniques of freezing have the potential to cause certain forms of quality degradation, such as harm to cellular structure, and heightened loss of moisture. Therefore, innovative techniques for freezing have been devised to mitigate the drawbacks. Certain naturally occurring biomaterials that possess environmentally friendly, sustainable, non-harmful, remarkably efficient properties and the freezing point regulators (such as antifreeze proteins) have been scientifically proven to manage the freezing and thawing cycle, thus demonstrating promising prospects for utilization in the realm of food and food-related sectors. The purpose of this review is to thoroughly investigate the advanced freezing methods, and the cryoprotective impact of antifreeze proteins (AFPs), emphasizing their function in the food freeze–thaw process. Moreover, this review highlights the advantages and challenges of AFP employment in food preservation. The characteristics of AFPs are derived from their ability to exhibit thermal hysteresis, alter the crystal morphology, and prevent the process of ice recrystallization. Hence, AFPs have been effectively utilized to maintain the quality of a diverse range of refrigerated and frozen food products as a potential cryoprotectant agent in food industry.